Evaluation of Clinical and Pathological Response in Breast Cancer Following Neoadjuvant Chemotherapy- A Single Institution Experience - Anju Farzana Abdul Gafoor; Priya Balakrishnan; KM Jagathnath Krishna; Asha Arjunan (Journal of Clinical and Diagnostic Research, 2022)
Introduction: In locally advanced breast cancer, Neoadjuvant Chemotherapy (NACT) is the mainstay of treatment. NACT is also considered as a potentially helpful treatment option in early-stage HER2 positive and triple-negative breast cancer. Aim: To assess pathological Complete Response (pCR) in patients with breast cancer who received NACT and to evaluate the association with clinical and pathological factors. Materials and Methods: The present retrospective analysis was conducted at Breast Oncology Division of Regional Cancer Centre, Thiruvananthapuram, Kerala, India, from January 2013 to December 2015. The data of patients with invasive breast cancer who received NACT were retrieved from medical records and analysed in August 2021. In the surgical pathology specimens, pCR was defined as ypT0 ypN0: no residual invasive cancer and/or in-situ cancer in the breast or axillary lymph nodes. All factors identified with univariate analyses were entered into multivariate analysis, and statistical analysis was done using logistic regression. The p-value <0.05 was considered significant. Results: This study included 586 breast cancer patients who received NACT, with mean age of 50.7 years. The proportion of postmenopausal patients was higher than premenopausal patients (56.3% vs 43.7%). Overall, 21.3% patients (125/586) attained pCR (ypT0 ypN0). In univariate analysis, factors associated with pCR were higher histologic grade (grade III) of tumour {Odds Ratio (OR): 2.879, 95% Confidence Interval (CI): 1.615-5.129, p-value=0.001)}, lower composite clinical stage (OR: 2.236, 95% CI: 1.468-3.408, p-value=0.001), lack of Oestrogen Receptor (ER) expression (OR: 3.23,95% CI: 2.10-4.968, p-value=0.001) and lack of Progesterone Receptor (PR) expression (OR: 4.396, 95% CI: 2.714-7.121, p-value=0.001). Higher grade of tumour (OR: 2.211, 95% CI: 1.179-4.146, p-value=0.013), lower composite clinical stage (OR: 2.033, 95% CI: 1.262-3.276, p-value=0.004) and lack of PR expression (OR: 3.823, 95% CI: 2.301-6.350, p-value=0.001) remained predictive variables in multivariate analysis after correction for the other variables. Conclusion: The lower composite clinical stage, lack of Progesterone Receptor (PR) expression and higher histologic grade of tumour are associated with good response to NACT in breast cancer patients.